Live Earth artistes leave hefty carbon footprint - Abd Razak, Dzulkifli (2007)
JULY 7,2007, or 070707, is a rare occurrence. As such, many marked the event with special commitments like marriages or working towards a better quality of life. The live Earth concert was one such commitment at a global level to highlight the climate crisis, bringing together more than 100 music artistes and two billion people. Whether Live Earth will have the same lasting impact as the 1987 Brundtland Commission (formally known as the World Commission on Environment and Development or WCED) is doubtful.